2004
DOI: 10.1211/0022357044418
|View full text |Cite
|
Sign up to set email alerts
|

Development of a single-dose stabilized poly(d,l-lactic-co-glycolic acid) microspheres-based vaccine against hepatitis B

Abstract: The purpose of this study was to develop a stable single-dose vaccine based on recombinant hepatitis B surface antigen (HBsAg) in poly(D,L-lactic-co-glycolic acid) (PLGA) microspheres, in which HBsAg was stabilized by a protein stabilizer (trehalose) and an antacid (Mg(OH)2). The microspheres were prepared by the double emulsion method and characterized by scanning electron microscopy. To neutralize the acids liberated by the biodegradable lactic/glycolic acid based polymer, we coincorporated into the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 27 publications
1
36
0
4
Order By: Relevance
“…Many studies in different disease models, indicated that long lasting immunity can be achieved by administration of PLGA particles, which can avoid the requirement of multiple injections of the conventional vaccines. 36,58,80 For example, protective humoral and cellular immunities that were achieved by a single-shot HBsAg adsorbed PLGA MPs were similar to the response induced by booster injection of alum adsorbed HBsAg vaccine. 58 Furthermore, a single subcutaneous injection of HBsAgloaded PLGA MSs in mice led to comparable antibody responses to those of three injections of HBsAg aluminum vaccine.…”
Section: Environmental Related Factorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Many studies in different disease models, indicated that long lasting immunity can be achieved by administration of PLGA particles, which can avoid the requirement of multiple injections of the conventional vaccines. 36,58,80 For example, protective humoral and cellular immunities that were achieved by a single-shot HBsAg adsorbed PLGA MPs were similar to the response induced by booster injection of alum adsorbed HBsAg vaccine. 58 Furthermore, a single subcutaneous injection of HBsAgloaded PLGA MSs in mice led to comparable antibody responses to those of three injections of HBsAg aluminum vaccine.…”
Section: Environmental Related Factorsmentioning
confidence: 89%
“…Therefore, this delivery system is able to be administrated as a single-shot carrier adjuvant in development of vaccines and can prevent the need for multiple doses in next generation vaccines. 80 In addition, a remarkably high and long-lasting immune response associated with strong protective capacity was achieved with a single dose administration of SPf66 encapsulated PLGA MSs in Aotusmonkeys. 81 These results provide additional evidence that PLGA particles can be applied as a delivery system to induce protective immunity after a single dose administration of a vaccine.…”
Section: Environmental Related Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that the preparation conditions did not cause any irreversible aggregation or cleavage of the antigen. In addition, in vitro immunogenicity was also measured by EIA/protein ratio (relative potency) determination as described in our previous studies (Jaganathan et al, 2004;Pawar et al, 2013). The CS and GC NPs showed an EIA/protein ratio of 1.0 ± 0.2 and 1.0 ± 0.1, respectively.…”
Section: Confirmation Of the Structural Integrity And Antigenicitymentioning
confidence: 92%
“…Proteins were visualized by coomassie blue staining. The same sample was also used to measure the in vitro antigenicity using an enzyme immunoassay (EIA) (Jaganathan et al, 2004;Pawar et al, 2013). Each sample (HBsAg extracted from the NPs) was diluted with 0.2% (w/v) BSA in PBS (pH 7.4) to get three different concentrations and examined against a linear fitting to the response of control standard sample.…”
Section: Antigen-loading Efficiencymentioning
confidence: 99%